2020
DOI: 10.1155/2020/6483427
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Effects of Three Mulberry Varieties on Silkworms in Torbat Heydarieh

Abstract: This research was conducted to evaluate and compare the performance of the silkworm hybrid p31×p32  reared with three varieties of mulberry leaves. In this study, the silkworms were fed with leaves from Kenmochi (Morus bombycis), native mulberry (Morus alba L.), and black mulberry (Morus nigra L.) trees and their influence on the leaf ingested, leaf digested, cocoon weight, efficiency of feed consumption to cocoon shell, efficiency of digested feed to cocoon shell weight, efficiency of digested feed to cocoon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 6 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…Different species of mulberry may have compositional differences and might lead to varying effects on B. mori growth and silk productions (Mahmood et al, 1987;Hussain et al, 2011c;Kanwal et al, 2018). In another study, the results showed the significant variations of silkworms when reared on different mulberry species (Alipanah et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…Different species of mulberry may have compositional differences and might lead to varying effects on B. mori growth and silk productions (Mahmood et al, 1987;Hussain et al, 2011c;Kanwal et al, 2018). In another study, the results showed the significant variations of silkworms when reared on different mulberry species (Alipanah et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…The domesticated species of two silkworms ( S. cynthia ricini and B. mori ) were sampled from the sericulture rearing unit at the Animal Rearing and Containment Unit (ARCU) at icipe. At icipe, captive populations of the Eri ( S. cynthia ricini ) and domestic ( B. mori ) silkworms were reared on castor ( Ricinus communis L.) and mulberry ( Morus alba L.) leaves, respectively, which are the primary host plants [ 24 , 25 ]. From each of the two domesticated species, 2100 pupae were collected and further divided into groups of 700 each (3 groups or samples per species).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the by-products also have various uses ranging from fertilizers in rural areas to pharmaceutical industries which could be tapped to increase the income of farmers and other societal groups in the long term [2]. Silk production has the potential to make a signi cant contribution to the economy of many countries where there is surplus labor, low costs of production, and willingness to adopt new technologies [3,4].…”
Section: Introductionmentioning
confidence: 99%